-2(x+3)+3=-20

Simple and best practice solution for -2(x+3)+3=-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+3)+3=-20 equation:


Simplifying
-2(x + 3) + 3 = -20

Reorder the terms:
-2(3 + x) + 3 = -20
(3 * -2 + x * -2) + 3 = -20
(-6 + -2x) + 3 = -20

Reorder the terms:
-6 + 3 + -2x = -20

Combine like terms: -6 + 3 = -3
-3 + -2x = -20

Solving
-3 + -2x = -20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -2x = -20 + 3

Combine like terms: -3 + 3 = 0
0 + -2x = -20 + 3
-2x = -20 + 3

Combine like terms: -20 + 3 = -17
-2x = -17

Divide each side by '-2'.
x = 8.5

Simplifying
x = 8.5

See similar equations:

| 3(2t+5)=35 | | -7.16+0.8c=1.2c | | 8/7=-8/9y | | 3p^2-9p=0 | | 16+6n+17=-18+3n | | 2x^2+20x^2+18x=0 | | S-1.5=-7 | | -19f=-18f-20 | | 5x-4(x+2)=-3 | | 6(2y-3)=4y-8-2y | | 5j=6j+9 | | 25=-m-9+3m | | 5x+5=4x+17 | | (x^2+6x-7)(2x^2-5x-3)=0 | | 8-7(y+2)= | | 17-7=-2 | | 2s^2+15=-11s | | b+9b+5=-9+3b | | -2(4n-4)=3-3n | | -2=7-3(2z+3) | | 280x+135y=83300 | | b-2.8=0.86+1 | | -1+2x=6+11 | | -13=5+2a | | (3x+24)=(8x-11) | | Y+(2.8)=4.3 | | 2.50+4.25g=15.25 | | 4x+34=-7(x-8) | | x^4-6x^3+9x^2+4x-1=0 | | 5/4u=1/8 | | 13x+19y+8z=72500 | | 10x-2x=32 |

Equations solver categories